Diagnostic efficacy of cell block method for vitreoretinal lymphoma - Kase, Satoru (Diagn Pathol, 2016)
BACKGROUND: Vitreoretinal lymphoma (VRL) is a life- and sight-threatening disorder. The aim of this study was to analyze the usefulness of the cell block method for diagnosis of VRL. METHODS: Sixteen eyes in 12 patients with VRL, and 4 eyes in 4 patients with idiopathic uveitis presenting with vitreous opacity were enrolled in this study. Both undiluted vitreous and diluted fluids were isolated during micro-incision vitrectomy. Cell block specimens were prepared in 19 eyes from diluted fluid containing shredding vitreous. These specimens were then submitted for HE staining as well as immunocytological analyses with antibodies against the B-cell marker CD20, the T-cell marker CD3, and cell proliferation marker Ki67. Conventional smear cytology was applied in 14 eyes with VRL using undiluted vitreous samples. The diagnosis of VRL was made based on the results of cytology, concentrations of interleukin (IL)-10 and IL-6 in undiluted vitreous, and immunoglobulin heavy chain gene rearrangement analysis. RESULTS: Atypical lymphoid cells were identified in 14 out of 15 cell block specimens of VRL (positive rate: 93.3 %), but in 5 out of 14 eyes in conventional smear cytology (positive rate: 35.7 %). Atypical lymphoid cells showed immunoreactivity for CD20 and Ki67. Seven cell block specimens were smear cytology-negative and cell block-positive. The cell block method showed no atypical lymphoid cells in any patient with idiopathic uveitis. CONCLUSIONS: Cell block specimens using diluted vitreous fluid demonstrated a high diagnostic sensitivity and a low pseudo-positive rate for the cytological diagnosis of VRL. The cell block method contributed to clear differentiation between VRL and idiopathic uveitis with vitreous opacity. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13000-016-0479-1) contains supplementary material, which is available to authorized users.